How much is a million - Schwartz, David M.; Kellogg, Steven (New York Lothrop, Lee & Shepard Books, 1985)
Text and pictures try to make possible the conceptualization of a million, a billion, and a trillion.
Keywords: Million (The number); Billion (The number); Trillion (The number); Number concept